Which UHC? Features for Equity and Universalism; Comment on "Universal Health Coverage for Non-Communicable Diseases and Health Equity: Lessons From Australian Primary Healthcare" - Rene Loewenson (Kerman University of Medical Sciences, 2022)
Equity and universality are implicit in universal health coverage (UHC), although ambiguity has led to differing interpretations and policy emphases that limit their achievement. Diverse country experiences indicate a policy focus on differences in service availability and costs of care, and neoliberal policies that have focused UHC on segmented financing and disease- focused benefit packages, ignoring evidence on financing, service, rights-based and social features that enable equity, continuity of care and improved population health. Public policies that do not confront these neoliberal pressures limit equity-promoting features in UHC. In raising the impetus for UHC and widening public awareness of the need for public health systems, coronavirus disease 2019 (COVID-19) presents an opportunity for challenging market driven approaches to UHC, but also a need to make clear the features that are essential for ensuring equity in the progression towards universal health systems.